Design and Construction of a Controlled Temperature Food Product Dryer Based on a Programmable Logic Controller (PLC) - Naim, Kurniawati; Thaha, Sarma; Ichwal, Muhammad Noor; Akbar, Muhammad; Iman, Muhammad Taufik (Jurnal Teknologi Elekterika, 2024)
Drying food products using traditional methods relying on sunlight takes a relatively long time, especially with unpredictable weather conditions. Essentially, artificial drying using heat-based equipment provides several advantages, including: independence from weather conditions, adjustable drying capacity, controlled temperature, no need for extensive space, controlled drying conditions, and guaranteed and uniform drying quality. Therefore, this design aims to create a food drying apparatus with PLC control. PLC is used as the controller for this drying apparatus, allowing automatic drying of certain types of food. In this design, we connect a DC motor to rotate the drying cylinder with a PLC device by creating a ladder diagram and determining the inputs and outputs in the CX-Programmer application. The design utilizes three inputs and two outputs. It is important that the I/O is readable by the PLC so that the system operates according to the programmed instructions.